Pengaruh Kurs, Jumlah Uang Beredar, Dan Bi Rate Terhadap Inflasi Di Indonesia - Dwi Anugrah; Dwi Widiarsih; Mizan Asnawi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the effect of exchange rate, money supply (JUB), and BI Rate on inflation in Indonesia during the period 2011–2023. This research employs multiple linear regression with the Ordinary Least Square (OLS) approach using annual time series data sourced from Bank Indonesia and the Central Bureau of Statistics. The partial test results show that exchange rate and money supply have no significant effect on inflation, while the BI Rate has a positive and significant effect. Simultaneously, all three variables significantly influence inflation. These findings highlight the BI Rate’s role as a key instrument in controlling inflation in Indonesia.